Integration between Glycolysis and Glutamate-Glutamine Cycle Flux May Explain Preferential Glycolytic Increase during Brain Activation, Requiring Glutamate - Hertz, Leif; Chen, Ye (Frontiers in Integrative Neuroscience, 2017)
The 1988 observation by Fox et al. (1988) that brief intense brain activation increases glycolysis (pyruvate formation from glucose) much more than oxidative metabolism has been abundantly confirmed. Specifically glycolytic increase was unexpected because the amount of ATP it generates is much smaller than that formed by subsequent oxidative metabolism of pyruvate. The present article shows that preferential glycolysis can be explained by metabolic processes associated with activation of the glutamate-glutamine cycle. The flux in this cycle, which is essential for production of transmitter glutamate and GABA, equals 75% of brain glucose utilization and each turn is associated with utilization of ~1 glucose molecule. About one half of the association between cycle flux and glucose metabolism occurs during neuronal conversion of glutamine to glutamate in a process similar to the malate-aspartate shuttle (MAS) except that glutamate is supplied from glutamine, not formed from α-ketoglutarate (αKG) as during operation of conventional MAS. Regular MAS function is triggered by one oxidative process in the cytosol during glycolysis causing NAD+ reduction to NADH. Since NADH cannot cross the mitochondrial membrane (MEM) for oxidation NAD+ is re-generated by conversion of cytosolic oxaloacetate (OAA) to malate, which enters the mitochondria for oxidation and in a cyclic process regenerates cytosolic OAA. Therefore MAS as well as the “pseudo-MAS” necessary for neuronal glutamate formation can only operate together with cytosolic reduction of NAD+ to NADH. The major process causing NAD+ reduction is glycolysis which therefore also must occur during neuronal conversion of glutamine to glutamate and may energize vesicular glutamate uptake which preferentially uses glycolytically derived energy. Another major contributor to the association between glutamate-glutamine cycle and glucose utilization is the need for astrocytic pyruvate to generate glutamate. Although some oxidative metabolism occurs during glutamate formation it is only one half of that during normal tricarboxylic acid (TCA) cycle function. Glutamate’s receptor stimulation leads to potassium ion (K+) release and astrocytic uptake, preferentially fueled by glycolysis and followed by release and neuronal re-accumulation. The activation-induced preferential glycolysis diminishes with continued activation and is followed by an increased ratio between oxidative metabolism and glycolysis, reflecting oxidation of generated glutamate and accumulated lactate.